Moralization in policy narratives: insights from the politics of climate change and public health - Bulian, Simon; Tosun, Jale; Becker, Maria (Policy studies journal, 2025)
In this study, we examine the process of moralization - defined as the use of moral values to mobilize support for or against policy proposals. Specifically, we investigate how political parties strategically employ moralization to influence policy processes, varying their approach depending on their political ideology and institutional position. We address several key questions: How do policy actors integrate moral values into policy narratives? Does their institutional position and policy-shaping power affect their use of moralization? Can ideology explain variation in moralization strategies? Our research combines theoretical refinement of the Narrative Policy Framework (NPF) with in-depth analysis of policy narratives from German political debates on climate change and the COVID-19 pandemic. Our findings indicate that both party ideology and institutional role (government versus opposition) explain variation in the degree and type of moralization employed in narratives. More broadly, our work suggests that the NPF, as a relatively new conceptual framework, would benefit from explicitly incorporating moral values and moralization, as these elements provide a more nuanced understanding of the diverse narratives used in policy processes.
Zuerst veröffentlicht: 13. Juni 2025
Gesehen am 20.10.2025